Enhancing creative writing skills through short story composition - Wardiah, Dessy; Kristiawan, Muhammad (Edelweiss Applied Science and Technology, 2025)
This study aims to systematically explore and analyze effective strategies for enhancing creative writing skills through short story-based approaches. Employing the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) methodology, the research reviewed literature from the Scopus and Semantic Scholar databases published between 2019 and 2024. Inclusion and exclusion criteria were applied to ensure the relevance and quality of the data, resulting in the selection of 13 studies from an initial pool of 59 articles. The findings reveal that a variety of instructional methods such as short story-based programs, creative-productive learning models, three-dimensional media, collaborative techniques, and film transformation demonstrably enhance students' creative writing competencies. These approaches not only foster creativity but also improve student motivation, engagement, and overall learning outcomes. The study concludes that integrating innovative and technological elements into writing instruction is vital for cultivating creative expression in educational settings. However, the limited scope of existing studies characterized by small sample sizes and a lack of longitudinal data highlights the need for further research employing more diverse samples and robust methodologies. Practically, educators are encouraged to adopt multifaceted, technology-supported strategies to effectively nurture students' creative writing skills.